Reforma agrária e estrutura fundiária no Brasil: uma análise a partir do I Plano Nacional de Reforma Agrária - Fleury, Renato Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research aims to discuss land reform policy and its impact on land concentration in Brazil from 1985 to 2010. The work historically reconstructed the process of formation and evolution of the Brazilian agrarian structure, showing the permanence it the following constituent features: high land concentration, exclusion from access to land for poor farmers, conflict and violence in the countryside and difficulty of land regulation by public authorities. During the phase of modernization of Brazilian agriculture, which lasted from mid-1960 to 1985 rose substantially land intended for incorporation into agricultural areas. In the most recent period, identified from 1985, the year in which it was implemented the First National Plan for Agrarian Reform (PNRA I) in the country, were revived hopes to reverse the previous historical trends, and the volume of land intended for layers of landless workers or those with little land through land policy also rose sharply between 1985 and 2010. Given these effects seen in the rural sector, this study established a comparison of coming impacts of agricultural land policies and modernizing with the impacts of policies of Agrarian Reform (PNRA I and II PNRA), comparing the evolution of the area destined to agricultural land mediated by agricultural modernization (1960 to 1985) with the evolution of land area distributed by the rural settlements program (1985-2010) performed by plans agrarian reform of the New Republic. Thus, it was the reason why the effects on indicators of land concentration in Brazil are still very significant

A presente pesquisa pretende discutir a política de reforma agrária e seu impacto sobre a concentração fundiária no Brasil no período de 1985 a 2010. O trabalho reconstruiu historicamente o processo de constituição e evolução da estrutura fundiária brasileira, mostrando a permanência nela dos seguintes traços constitutivos: elevada concentração fundiária, exclusão do acesso a terra para agricultores pobres, conflito e violência no campo e dificuldade de regulação fundiária por parte das autoridades públicas. Durante a fase de modernização da agricultura brasileira, que durou de meados de 1960 até 1985, elevou-se substancialmente a incorporação de terras destinadas às áreas agriculturáveis. Em período mais recente, identificado a partir de 1985, ano em que foi implementado o I Plano Nacional de Reforma Agrária (I PNRA) no país, foram reavivadas esperanças no sentido de reverter as tendências históricas anteriores, e o volume de terras destinado às camadas de trabalhadores rurais sem terra ou com pouca terra por meio da política fundiária também aumentou bastante entre 1985 e 2010. Diante desses efeitos constatados no setor rural, este estudo estabeleceu um confronto dos impactos oriundos das políticas agrícolas e agrárias modernizadoras com os impactos gerados pelas políticas de reforma agrária (I PNRA e II PNRA), comparando a evolução da área destinada às terras agriculturáveis mediadas pela modernização agrícola (1960-1985) com a evolução da área de terras distribuídas pelos programas de assentamentos rurais (1985-2010) executados pelos planos de reforma agrária da Nova República. Deste modo, verificou-se o motivo pelo qual os efeitos sobre indicadores de concentração fundiária no Brasil ainda são pouco significativos
Keywords: INCRA; Reforma agraria; Reforma agraria - Brasil; Estrutura agraria; Política social; Social policy